Analysis of Seismic Damage of Underground Powerhouse Structure of Hydropower Plants Based on Dynamic Contact Force Method. (2nd September 2014) - Yang, Yang; Chen, Juntao; Xiao, Ming
Abstract : Based on the characteristics of the dynamic interaction between an underground powerhouse concrete structure and its surrounding rock in a hydropower plant, an algorithm of dynamic contact force was proposed. This algorithm enables the simulation of three states of contact surface under dynamic loads, namely, cohesive contact, sliding contact, and separation. It is suitable for the numerical analysis of the dynamic response of the large and complex contact system consisting of underground powerhouse concrete structure and the surrounding rock. This algorithm and a 3D plastic-damage model were implemented in a dynamic computing platform, SUCED, to analyze the dynamic characteristics of the underground powerhouse structure of Yingxiuwan Hydropower Plant. By comparing the numerical results and postearthquake investigations, it was concluded that the amplitude and duration of seismic waves were the external factors causing seismic damage of the underground powerhouse structure, and the spatial variations in structural properties were the internal factors. The existence of rock mass surrounding the underground powerhouse was vital to the seismic stability of the structure. This work provides the theoretical basis for the anti-seismic design of underground powerhouse structures.